Factors Affecting Voluntary Staff Turnover: A Case Study Of Springs Parklands Hospital, South Africa - Abhinanda Gautam; Ikhona Tuswa (European Scientific Journal, ESJ, 2016)
The aim of this study is to examine the relationship between perceived availability of opportunities for promotion, training, career progression, existing management style and voluntary staff turnover intention among the nurses working at Springs Parklands Hospital. A quantitative, descriptive correlational design is used. Full time staff nurses (N= 200) were surveyed. The findings revealed that all the four variables were significantly and negatively correlated to the intention to quit and predicted (16.8%) of the variance in intention to leave scores. Management style is the strongest predictor of intent to leave (14.5%). Nurses perceiving their managers as participatory had lower intention to leave. To retain qualified personnel, hospital administrators should focus on participative management style and career development programs that address the needs of the staff and the hospital.